2021
DOI: 10.33715/inonusaglik.840222
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Nursing Students' Individual Innovativeness Levels and Attitudes to Evidence-Based Nursing

Abstract: Bu çalışma hemşirelik öğrencilerinin bireysel yenilikçilik düzeylerinin kanıta dayalı hemşireliğe yönelik tutumları ile ilişkisinin belirlenmesi amacıyla yapılmıştır. Tanımlayıcı, kesitsel ve ilişki arayıcı tipte olan bu çalışma, bir devlet üniversitesinin hemşirelik bölümü 2., 3. ve 4. sınıfında öğrenim gören öğrencileri (n=322) ile yapılmıştır. Araştırmada örneklem seçimine gidilmemiş ve araştırmaya katılmaya gönüllü olan öğrenciler alınmıştır. Veriler, “Öğrenci Tanıtım Formu”, “Bireysel Yenilikçilik Ölçeği”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
3
0
2
Order By: Relevance
“…22 The results of the study in Türkiye have revealed that nursing students are in early majority or late majority category. 12,13 When the international literature is examined, the innovativeness scores of nursing students were found to be moderately high in a study conducted in Taiwan. 23 Similarly, a study examining the correlation between information seeking behavior and innovative behaviors of Chinese nursing students reported that the students had a high level of innovativeness behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 The results of the study in Türkiye have revealed that nursing students are in early majority or late majority category. 12,13 When the international literature is examined, the innovativeness scores of nursing students were found to be moderately high in a study conducted in Taiwan. 23 Similarly, a study examining the correlation between information seeking behavior and innovative behaviors of Chinese nursing students reported that the students had a high level of innovativeness behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Baltacı and Metin evaluated the relationship between students' individual innovation level and evidence-based nursing attitudes, and determined that as the individual innovativeness level increased, their attitudes towards evidence-based nursing improved. 13 A study conducted with senior nursing students revealed a positive correlation between individualized care and individual innovativeness scores, and it was revealed that innovator students who produced, developed and implemented individualized nursing programs or projects had high perceptions of care. 10…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kişisel Bilgi Formu: Araştırmacı tarafından literatür doğrultusunda geliştirilmiştir. 7,8,11 Formda; hemşirelik öğrencilerinin sosyo-demografik özelliklerini, sınıfını, anne ve babasının eğitim durumunu ve mesleğini belirlemeye yönelik 10 soru yer almaktadır. Ölçekten 18-90 arası puan alınmaktadır.…”
Section: Veri Toplamaunclassified
“…6 Bu nedenle, eğitimcilerin hemşirelik öğrencilerini mesleki eğitimlerinde mezun olduktan sonra meslek hayatlarında karşılaşabilecekleri zorluklarla yüzleşmeye hazırlarken, hem kişisel hem de profesyonel yaşamda önemli olan duygusal zekanın geliştirilmesinin gerekliliği üzerinde durulmaktadır. 7 Hemşirelik öğrencilerinin duygusal zekaları ve bireysel yenilikçilikleri ile ilgili çalışmalar yapılmış olsa da [6][7][8][9][10] duygusal zeka ile bireysel yenilikçilik düzeyleri arasındaki ilişkiyi inceleyen koyan bir araştırmaya ulaşılamamıştır. Bu açıdan, hemşirelik öğrencilerinin duygusal zekâ ve bireysel yenilikçilik düzeylerinin ve aralarındaki ilişkinin belirlenmesinin amaçlandığı bu araştırma hem literatüre hem de yeni uygulamalara katkı sağlaması açısından önem taşımaktadır.…”
unclassified